(untitled) (Homoeopathy for All, 2024)
This case demonstrates the effectiveness of Boenninghausen’s method and his less often used repertory Boenninghausen’s Therapeutic Pocket Book. This is one of the earliest repertories which based on primary proving data source work of Hahnemann. However, Therapeutic Pocket Book is less used in practice because of Kent’s influences. By using Boenninghausen’s Therapeutic Pocket Book we are able to reduce the discomfort in patients with urolithiasis.